2018
DOI: 10.1002/jts.22310
|View full text |Cite
|
Sign up to set email alerts
|

The Child Trauma Screen: A Follow‐Up Validation

Abstract: Although the prevalence of exposure to potentially traumatic events and associated outcomes among children is well documented, widespread trauma screening remains limited. This study provides additional data supporting the psychometrics of the Child Trauma Screen (CTS), a free, brief, empirically derived measure that was intended as a trauma screen for use across child-serving systems. Participants were an ethnically diverse sample of 187 children aged 6-18 years recruited from an urban children's community me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 32 publications
0
22
0
2
Order By: Relevance
“…Child post‐traumatic stress disorder (PTSD) symptoms were assessed using mother and child report on the Child Trauma Scale symptoms scale (Lang & Connell, 2017), which includes six items assessing DSM PTSD symptoms over the prior 30 days. The analysis used a total score and a cut point of ≥6 for both child and parent reports (Lang & Connell, 2018).…”
Section: Methodsmentioning
confidence: 99%
“…Child post‐traumatic stress disorder (PTSD) symptoms were assessed using mother and child report on the Child Trauma Scale symptoms scale (Lang & Connell, 2017), which includes six items assessing DSM PTSD symptoms over the prior 30 days. The analysis used a total score and a cut point of ≥6 for both child and parent reports (Lang & Connell, 2018).…”
Section: Methodsmentioning
confidence: 99%
“…However, this sample is representative of the urban community in which the primary care practice was located and prior research on the CTS has included more diverse and representative samples by race/ethnicity. 21,22 Given somewhat higher rates of trauma exposure and adversity among ethnic minority populations 27 and the location of the study clinic in a large urban area, the rates of trauma exposure and reactions found in the current study may be higher than the general population. Finally, we did not collect data about the utility of trauma screening and to what extent screening helped or hindered the primary care visit and/or referral to or receipt of behavioral health services, which could be a focus of future research.…”
Section: Discussionmentioning
confidence: 71%
“…An RI-5 total score of 35 or greater (indicating likely PTSD diagnosis) was used as the criterion variable 24 ; 3.5% of caregiver reports and 10.3% of youth reports met this criterion. At a score of 6 or greater, established in 2 prior validation studies based on clinical samples, 21,22 caregiver sensitivity was 1.00 and specificity was 0.85, with 85% of youth correctly classified. For youth, a score of 6 or greater resulted in sensitivity of 0.88, specificity of 0.72, and correct classification of 85% of cases.…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations